2017
DOI: 10.1016/j.fsigss.2017.09.140
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding and Atlantic reef fishes: The molecular identification of a reef fish community from the Todos os Santos Bay, Bahia, Brazil

Abstract: A B S T R A C TThe reef fish community is one of the most explored fish stock by local and medium scale fishing activities as well as by the international ornamental fish trade. Despite these intense commercial activities, several reef species are poorly known. The reef fish community limited knowledge makes difficult the commercial regulation and also the adoption of conservation policies and general law enforcement. The present study deals with the molecular identification of a reef fish community from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…dentex specimens to three different MOTUs, as confirmed by the haplotype network and the genetic divergence of 4.0% to 9.3% between the lineages. These findings are consistent with the hypothesis of cryptic speciation within Odontoscion proposed by Duarte et al [ 12 ], who, using DNA barcoding, identified two groups with a divergence of 12.9% between the Caribbean and Brazilian provinces. Lineages I and II of O .…”
Section: Discussionsupporting
confidence: 92%
“…dentex specimens to three different MOTUs, as confirmed by the haplotype network and the genetic divergence of 4.0% to 9.3% between the lineages. These findings are consistent with the hypothesis of cryptic speciation within Odontoscion proposed by Duarte et al [ 12 ], who, using DNA barcoding, identified two groups with a divergence of 12.9% between the Caribbean and Brazilian provinces. Lineages I and II of O .…”
Section: Discussionsupporting
confidence: 92%
“…The mean K2P genetic distances hierarchy increased with increased taxonomic level, consistent with data from coral reef fishes of the Indo-Malay-Philippines Archipelago, Todos os Santos Bay, and marine fish of other areas (Lakra et al, 2011;Hubert et al, 2012;Duarte et al, 2017). Similar results were also found for freshwater fishes (Hubert et al, 2008;Barman et al, 2018).…”
Section: Genetic Divergencesupporting
confidence: 86%
“…Because of their cryptic habitats, dinematichthyids are rarely observed or collected with conventional methods (Robertson & Smith-Vaniz, 2008), even in relatively well-sampled areas such as the Todos os Santos Bay and the Abrolhos Bank, in north-eastern Brazil (e.g. Cruz et al, 2015;Duarte et al, 2017;Dutra et al, 2005;Ferreira et al, 2015). Species identification is also hindered by the overall weak informative power of morphometric and meristic data (Møller et al, 2004).…”
Section: Diagnosismentioning
confidence: 99%